Characterization of the public administration principles in the EU Member States - Baranov , Andriy (Theory and Practice of Public Administration, 2019)
The article describes the basic principles of public administration and administration in EU Member States, which are based on administrative law common to Western European countries, and includes such groups of principles as reliability and predictability (legal certainty); openness and transparency; accountability; efficiency and effectiveness. The administrative and legal mechanism implementation the public administration democratic principles system has been determined. These principles are enshrined in the only binding legal instrument for the general regulation of the prevention of corruption among public servants and public figures in EU Member States, including the UNCAC (United Nations Convention against Corruption), the descriptions in the UNCAC Technical Guide (which has an advisory function) and soft tools. policies (adopted in this area by the EU, the CoE and the OECD), including codes of conduct, principles, recommendations and guidelines as set out in the Council of Europe Model Code of Conduct for Civil Servants and the OECD Principles on Ethics Management in erzhavniy service. The article states that there is no acquis communautaire for EU member states that would set a requirement for an objective, responsible, honest and transparent public sector. The preconditions for transparent and effective democratic governance, however, are the above principles, which play a fundamental role in the process of European integration, enabling major reforms and effective dialogue with the European Union, and are criteria for EU enlargement in order to create a strong national public administration system. In doing so, the government’s attention to specific principles may vary depending on the country, depending on the country’s governance structure, administrative culture, previous reforms and key issues of the particular country; the monitoring structure establishes a consistent set of requirements for all countries, giving each country some flexibility in defining its tasks.